ANALISIS PENGARUH STOCK SELECTION SKILL, MARKET TIMING ABILITY, TOTAL ASSET, DAN EXSPENSE RATIO TERHADAP KINERJA REKSA DANA SYARI’AH DI INDONESIA PERIODE 2013-2016 - Fitri Andriani, Lia; Mawardi, Wisnu (Diponegoro Journal of Management, 2018)
Mutual funds are one of the alternative choices for investment for the community, especially for people who have small capital, people do not have time to take care of their investments or people who do not have expertise in account the risks faced on their investment. Shari'a Mutual funds are mutual funds operates according to the provisions and principles of the Islamic Shari'a.  This research conducted to examine the relationship between the performance of mutual fund with Sharpe’s measurement to the affecting variables, such as stock selection skill, market timing ability, total asset, and expense ratio.  The data used in this research are monthly data on SBI, JII, shari’a mutual fund return, risk free, andNet Asset Value (NAV) of 21 sampe of mutual funds Shari’a for 2013-2016.  The reasearch shows that total asset, and expense ratio have positive and insignificant effect on Shari’a mutual fund performance.  Stock selection skill and market timing ability have a positive and significant effect on Shari’a mutual fund performance.  Simultaneous testing shows stock selection skill, market timing ability, total asset, and expense ratio have a significant positive impact to the performance of equity mutual fund Shari’a.